Compensatory Function of Pyk2 Protein in the Promotion of Focal Adhesion Kinase (FAK)-null Mammary Cancer Stem Cell Tumorigenicity and Metastatic Activity - Fan, Huaping (American Society for Biochemistry and Molecular Biology, 2011)
Mammary cancer stem cells (MaCSCs) have been identified as a rare population of cells capable of self-renewal to drive mammary tumorigenesis and metastasis. Nevertheless, relatively little is known about the intracellular signaling pathways regulating self-renewal and metastatic activities of MaCSCs in vivo. Using a recently developed breast cancer mouse model with focal adhesion kinase (FAK) deletion in mammary tumor cells (MFCKO-MT mice), here we present evidence suggesting a compensatory function of Pyk2, a FAK-related kinase, in the regulation of MaCSCs and metastasis in these mice. Increased expression of Pyk2 was found selectively in pulmonary metastatic nodules of MFCKO-MT mice, and its inhibition significantly reduced mammary tumor development and metastasis in these mice. Consistent with the idea of metastasis driven by MaCSCs, we detected selective up-regulation of Pyk2 in MaCSCs, but not bulk mammary tumor cells, of primary tumors developed in MFCKO-MT mice. We further showed that inhibition of Pyk2 in FAK-null MaCSCs significantly decreased their tumorsphere formation and migration in vitro as well as self-renewal, tumorigenicity, and metastatic activity in vivo. Last, we identified PI3K/Akt signaling as a major mediator of FAK regulation of MaCSCs as well as a target for the compensatory function of Pyk2 in FAK-null MaCSCs. Together, these results further advance our understanding of FAK and its related tyrosine kinase Pyk2 in regulation of MaCSCs in breast cancer and suggest that pharmaceutically targeting these kinases may hold promise as a novel treatment for the disease by targeting and eradicating MaCSCs.